Answer:
.
Step-by-step explanation:
![2 {x}^{2} - 5x - 3](https://tex.z-dn.net/?f=2%20%7Bx%7D%5E%7B2%7D%20%20-%205x%20-%203)
The answer of this question is b
Answer:
A the first one
Step-by-step explanation:
Hello! To solve for x means to isolate x:
y = x^2 + 7
y - 7 = x^2
sqrt(y - 7) = x
Answer:
x = sqrt(y - 7)
Hope this helps!
Answer:
![23x - 10](https://tex.z-dn.net/?f=%2023x%20-%2010%20)
Step-by-step explanation:
To the find the equivalent of
, evaluate the expression. Start by opening the bracket.
![9*2x - 9*3 + 5x + 17](https://tex.z-dn.net/?f=%209%2A2x%20-%209%2A3%20%2B%205x%20%2B%2017%20)
![18x - 27 + 5x + 17](https://tex.z-dn.net/?f=%2018x%20-%2027%20%2B%205x%20%2B%2017%20)
Pair like terms
![18x + 5x - 27 + 17](https://tex.z-dn.net/?f=%2018x%20%2B%205x%20-%2027%20%2B%2017%20)
![23x - 10](https://tex.z-dn.net/?f=%2023x%20-%2010%20)
The equivalent of
is ![23x - 10](https://tex.z-dn.net/?f=%2023x%20-%2010%20)